The Representation of Target Culture in a Locally Published English Textbook - Rizki Muhammad Ardian Setiadi; Daniel Simanjuntak; Mohammad Santosa Mulyo Diningrat (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
Culture is an important part of English language teaching and learning. Students must be exposed to the culture related to the communication skills being taught. Textbook can be a medium for the teachers to present different kinds of culture along with the language content. Therefore, it is essential for an English textbook to properly include cultural contents. This study aims to investigate the target culture included in a junior high school English textbook used by many teachers in Indonesia. Qualitative descriptive design was employed in order to describe the target culture in the textbook without any manipulation to the data. Moran’s (2001) five dimensions of culture that include products, practices, perspectives, communities, and persons was used to analyze the data. The results found 61 items in the textbook that contained references to the target culture. The ways those target culture were presented were not vary. Almost all of those items were presented in words or passages.